ANALISIS PENGGUNAAN INPUT PRODUKSI PADI SAWAH DI DESA TORIBULU KECAMATAN TORIBULU KABUPATEN PARIGI MOUTONG - Rahmasita Rahmasita; Max Nur Alam; Christoporus Christoporus (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
The objective of this research is to determine the influence of input factors such as land area, seeds, urea fertilizer, phonska fertilizer, and labor on the production of lowland rice in Toribulu village, Toribulu sub district, Parigi Moutong district. The study was conducted between 29 November 2019 and 8 January 2020, and 37 out of 240 individuals were randomly selected as respondents for the study. The Cobb Douglass production function was used for analysis, and the results indicate that the combination of all input factors simultaneously has a significant effect on the production. However, individually, only land area, seeds, and urea fertilizer had a significant effect on production, while phonska fertilizer and labor had no significant effect. The significance level was 0.000, which is less than the 5% level of significance.